A rare case report of primary ovarian carcinoid presenting with constipation - Deng, Xiaofeng; Huang, Qian; Xie, Bangfang; Huang, Hailong; Chen, Jianguo (Frontiers in Oncology, 2025)
BackgroundOvarian carcinoids are exceptionally rare. This report discusses an unprecedented case of a primary ovarian mixed insular and trabecular carcinoid, presenting with constipation.Case PresentationA 47-year-old female presented with a four-month history of constipation. A comprehensive abdominal CT with contrast revealed a large mass in the pelvic region, measuring 8.6×9.7×9.3cm. Consequently, the patient was referred for further evaluation. Intraoperative exploration uncovered a 10.0×9.0 cm mass in the left ovary. Initial histopathological assessment suggested a sex cord-stromal cell tumor, leading to a left ovariectomy and bilateral salpingectomy. Final histopathological analysis post-surgery identified the mass as a mixed insular and trabecular carcinoid. The patient was diagnosed with stage Ia, T1aN0M0 primary ovarian mixed insular and trabecular carcinoid.ConclusionsDiagnosis of carcinoids predominantly relies on postoperative histopathological examination. As of now, There is no established standard treatment, emphasizing the necessity for ongoing patient monitoring.